Changes in Iron Availability with Roxadustat in Nondialysis- and Dialysis-Dependent Patients with Anemia of CKD. Issue 9 (29th September 2022) - Pergola, Pablo E.; Charytan, Chaim; Little, Dustin J.; Tham, Stefan; Szczech, Lynda; Leong, Robert; Fishbane, Steven
Visual Abstract: Abstract : Key Points: Roxadustat increases hemoglobin and serum iron levels in nondialysis- and dialysis-dependent patients with anemia of CKD. As roxadustat improves iron kinetics, less intravenous iron supplementation is required versus placebo or epoetin alfa. Background: Roxadustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor, increases hemoglobin by stimulating erythropoietin synthesis and improving iron availability through facilitation of iron uptake and/or release from stores. In this exploratory analysis, we assessed the effect of roxadustat treatment on laboratory parameters related to iron metabolism in patients with anemia of chronic kidney disease (CKD). Methods: Data were pooled from pivotal, randomized, phase 3 roxadustat trials: three placebo-controlled, double-blind trials in nondialysis-dependent (NDD) CKD and three open-label, active-comparator (epoetin alfa) trials in dialysis-dependent (DD) CKD. In this exploratory analysis, mean changes from baseline in hemoglobin, iron parameters, and hepcidin, and intravenous (iv) iron use were evaluated. Pooled results in NDD CKD and DD CKD patients are reported. Results: Overall, 4277 patients with NDD CKD and 3890 patients with DD CKD were evaluated. Hemoglobin increases with roxadustat treatment were accompanied by increases in serum iron and total iron-binding capacity (TIBC) and decreases in serum ferritin and hepcidin from baseline through week 52. With epoetin alfa, the hemoglobin increase was accompanied by decreases in serum ferritin and hepcidin, but serum iron decreased, and there was no change in TIBC. With placebo, there were no changes in hemoglobin, iron parameters, or hepcidin. During treatment, iv iron use was reduced with roxadustat versus placebo and epoetin alfa. Conclusions: In patients with NDD CKD and DD CKD, roxadustat treatment is associated with increases in serum iron and TIBC, accompanied by reduced hepcidin and indicative of improved iron kinetics. Patients treated with roxadustat achieved target hemoglobin levels with less iv iron use versus comparators. Practitioners treating patients with anemia of CKD with roxadustat should consider its unique effects when interpreting iron parameters.